A model-independent tripartite test of cosmic distance relations - Matos, Isabela [UNESP]; Quartin, Miguel; Amendola, Luca; Kunz, Martin; Sturani, Riccardo [UNESP] (IOP Publishing, 2024)
Cosmological distances are fundamental observables in cosmology. The luminosity (D L), angular diameter (D A) and gravitational wave (D GW) distances are all trivially related in General Relativity assuming no significant absorption of photons in the extragalactic medium, also known as cosmic opacity. Supernovae have long been the main cosmological standard candle, but bright standard sirens are now a proven alternative, with the advantage of not requiring calibration with other astrophysical sources. Moreover, they can also measure deviations from modified gravity through discrepancies between D L and D GW. However, both gravitational and cosmological parameters are degenerate in the Hubble diagram, making it hard to properly detect beyond standard model physics. Finally, recently a model-independent method named FreePower was proposed to infer angular diameter distances from large-scale structure which is independent of the knowledge of both early universe and dark energy physics. In this paper we propose a tripartite test of the ratios of these three distances with minimal amount of assumptions regarding cosmology, the early universe, cosmic opacity and modified gravity. We proceed to forecast this test with a combination of LSST and Roman supernovae, Einstein Telescope bright sirens and a joint DESI-like + Euclid-like galaxy survey. We find that even in this very model-independent approach we will be able to detect, in each of many redshift bins, percent-level deviations in these ratios of distances, allowing for very precise consistency checks of ΛCDM and standard physics. It can also result in sub-percent measurements of H 0
Keywords: cosmological parameters from LSS; galaxy surveys; Gravitational waves in GR and beyond: theory; supernova type Ia - standard candles